Az „új közgazdaságtanról” - Polányi Károly kölcsönbe vett szemüvegén keresztül... (Heurisztika és program) - Balázs, Krémer (Szociologiai Szemle, 2016)
This paper aims at interpreting Polanyi's theory on substantive and embedded economy as a possible insight to interpret rich empirical findings of “new economics”. Key phenomena and concepts of Polanyi, especially the “latent commodities” may provide new explanations on how inappropriate political regulations and social conventions biased the integration of land (natural resources), labor and money into past-decades markets, and how led to crises. As a hypothesis the paper suppose more about the relevance of Polanyi's theory by contributing to overcome the crisis of the sociology. Mainstream economic, social and human sciences seek how human and social nature causes biases and fallacies in market mechanisms. Following Polanyi's inspirations, the question should be reversed: the sociological question is not how society impact markets, but rather, how markets contribute to substantive and embedded economy, both on micro (household) and macro (markets, redistribution-welfare state, and reciprocity - new kinships and civic society) levels. (English)
Sociology
Keywords: Polányi; beágyazódottság; embedded economy; substantive economy; szubsztantív gazdaság; új közgazdaságtan